Ascites and Encapsulating Peritonitis in Endometriosis: a Systematic Review with a Case Report - Thais Fontes de Magalhães; Kathiane Lustosa Augusto; Livia Ponte Mota; Arthur Ribeiro da Costa; Rainardo Antonio Puster; Leonardo Robson Pinheiro Sobreira Bezerra (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2018)
Abstract Endometriosis can have several different presentations, including overt ascites and peritonitis; increased awareness can improve diagnostic accuracy and patient outcomes. We aimto provide a systematic review and report a case of endometriosis with this unusual clinical presentation. The PubMed/MEDLINE database was systematically reviewed until October 2016. Women with histologically-proven endometriosis presenting with clinically significant ascites and/or frozen abdomen and/or encapsulating peritonitis were included; thosewith potentially confounding conditionswere excluded.Our search yielded 37 articles describing 42 women, all of reproductive age. Ascites was mostly hemorrhagic, recurrent and not predicted by cancer antigen 125 (CA-125) levels. In turn, dysmenorrhea, dyspareunia and infertility were not consistently reported. The treatment choices and outcomes were different across the studies, and are described in detail. Endometriosis should be a differential diagnosis of massive hemorrhagic ascites in women of reproductive age.